PERANCANGAN SISTEM INFORMASI AKADEMIK SEKOLAH BERBASIS WEB PADA SMP SARIPUTRA JAMBI - Susanto, Rudi (Universitas Pendidikan Indonesia, 2020)
The design of a school academic information system that includes information including announcements, study schedules, activity schedules, school calendars, and school information on Sariputra Jambi Junior High School. The system is designed to function to manage data on student grades, student data, teacher data, class data and subject data that are inputted by the teacher or class teacher. The system is designed to allow parents of students to access the system to see information about the value of their children and input from teachers for their children, as well as provide input to the school. The system designed can produce reports on student learning outcomes at Sariputra Jambi Junior High School. System modeling using UML (Unified Modeling Language), namely usecase diagrams, activity diagrams and class diagrams. The system design uses the PHP programming language and MySQL Database. The objectives of this research are to analyze and study the current school academic system at Sariputra Jambi Junior High School, produce a web-based school academic system at Sariputra Jambi Junior High School, and produce a system that can manage student grades data by teachers and can be accessed by parents.